Sovereign credit ratings: reframing the orthodox paradigm - Choy, Swee Yew (2021)
This dissertation makes an inquiry into the contested and variegated perspectives of the determinants of sovereign credit ratings given the need to understand both orthodox and unorthodox narratives which drive sovereign rating assessments. Unlike prior studies on sovereign ratings, this dissertation employs a novel approach through exploratory factor analysis, a dimension reduction approach and quantitative grounded theory to distill key factors influencing sovereign ratings. Furthermore, conventional research on sovereign ratings adopt an orthodox and limited selection of variables in their regression analysis, whereas this dissertation engages a large variable set before selecting significant variables through panel regression analysis. The relevance of both the factor approach and the use of unorthodox variables which differ from existing academic literature is validated by methodologies applied by the major credit rating agencies. The results of the panel regression and exploratory factor analysis in this research are systematically compared against existing literature, in order to categorise both orthodox and unorthodox factors and variables, forming a structured basis for theory generation. Consequently, the amalgamation of the empirical results through quantitative grounded theory develop a novel paradigm of sovereign credit ratings, expanding the scope of narratives influencing its determinants. The results suggest methodological refinements in approaching sovereign ratings need to be made. Furthermore, sovereign ratings prioritise the factors of external financial strength, institutional and socio-political quality over other factors. Among others, the discovered unorthodox narratives which influence sovereign ratings include public sector financial health and banking system quality.